Sustainable and responsible investment portfolio performance analysis in Indonesia Stock Exchange - Natasha Angelica; Cynthia Afriani Utama (Jurnal Keuangan dan Perbankan, 2020)
This study is intended for knowing the Sustainable and Responsible Investment (SRI) stock portfolio performance in the Indonesia Stock Exchange (IDX). SRI is a concept where the investor is not only considering financial performance, but also non-financial aspects in the company such as Environmental, Social, and Governance (ESG). The main objective of this study is to compare the performance of the SRI portfolio with the performance of comparable portfolios. Is the performance of the SRI portfolio in IDX better than conventional portfolio and Islamic portfolio? To answer this question, the SRI portfolio will be formed from SRI-KEHATI Index (SRI), a conventional portfolio will be formed from the LQ45 index, and the Islamic portfolio will be formed from Jakarta Islamic Index (JII). The performances of those three portfolios will be compared based on alpha value, Sharpe Ratio, Treynor Ratio, and Sortino Ratio. This study result shows that the SRI portfolio performance in IDX is better than the conventional portfolio and Islamic portfolio. That performance occurs because the average of SRI portfolio excess return has positive value during the study period. JEL Classification: F64, G11, G32DOI: https://doi.org/10.26905/jkdp.v24i3.4338